The Role of Parents in The Popularity of Finswimming Sports in Cimahi City - R Rizky Mahardika Raharja; Bambang Gatot Sugiarto; Sriningsih (Journal of Physical and Outdoor Education, 2025)
This study aims to identify the factors influencing the role of parents in the popularity of finswimming, as well as its main factors. Parental roles are considered one of the key factors in the development of sports, particularly for children and adolescents. The research method employed was a quantitative descriptive approach using a survey methodology, involving a total sample of 65 parents from the Siliwangi Aquatic Club Cimahi, Surya Gemilang Diving Club, and Best One Aquatic. The research results indicate that there are six factors influencing the role of parents: economic factors, communication factors, knowledge and awareness factors, educational factors, social and cultural factors, and the provision of sports equipment. Most parents have a high awareness of the importance of finswimming, provide economic support, supply equipment, and actively build social support. However, challenges such as inconsistency in accompaniment, uncertainty in prioritizing education over sports, and the primary influence factor of parental role—knowledge and awareness—were identified. Overall, parental support significantly influences children's participation and interest in finswimming, leading to the conclusion that parental role is a key factor in enhancing the popularity of finswimming in Cimahi City.